NF-κB Enhances Androgen Receptor Expression through 5′-UTR Binding in Gingival Cells. (October 2015) - Chang, J.H.; Wang, L.F.; Lu, S.L.; Huang, C.F.; Lu, H.K.
Dihydropyridine-induced gingival overgrowth (DIGO) is a side effect observed in patients treated for hypertension. The disease is aggravated by inflammation. Nifedipine (Nif), a dihydropyridine, causes gingival overgrowth by increasing the expression of the androgen receptor (AR). Furthermore, the proinflammatory cytokine interleukin 1β (IL-1β) induces collagen α1(I) expression through the AR in DIGO fibroblasts. These observations prompted us to investigate whether and how nuclear factor kappa B (NF-κB) affects AR expression in DIGO. Therefore, gingival fibroblasts obtained from the tissues of patients with DIGO and healthy subjects were stimulated with IL-1β, Nif, or both. mRNA and protein expression was detected with real-time polymerase chain reaction and Western blotting. High correlation coefficients were observed for the mRNA expression of the AR, connective tissue growth factor, and collagen α1(I) induced by both drugs. Western blot analysis showed that IL-1β and Nif increased and activated NF-κB more in DIGO cells than in healthy cells. An electrophoretic mobility shift assay demonstrated that the promoter and 5′-untranslated regions (5′-UTRs) of the AR gene contains 3 binding sites for the NF-κB p65 subunit. A chromatin immunoprecipitation assay revealed that the NF-κB p65 subunit was associated with AR 5′-UTRs in gingival fibroblasts. A site-directed mutagenesis study indicated that a mutation of NF-κB binding sites reduced Nif- and IL-1β-induced AR promoter activities. Collectively, these data indicate that NF-κB is an essential transcriptional regulator of AR gene expression and thus plays a crucial role in collagen overproduction in DIGO fibroblasts.